The Impact of Total Productive Maintenance (TPM) as Mediator between Total Quality Management (TQM) and Business Performance - Md Fauzi Ahmad; Shafeeka Fadlikh Zamri; Yunos Ngadiman; Chan Shiau Wei; Norhadilah Abdul Hamid; Ahmad Nur Aizat Ahmad; Mohd Nasrun Mohd Nawi; Nor Aida Abdul Rahman (International Journal of Supply Chain Management, 2019)
Total quality management (TQM) is importance management tool for every industry to compete in global market. However, based on previous TQM literature reported that ambiguous or mixed relationship between TQM and business performance and lack of examining moderator and mediator in previous work. Furthermore, there lack of study of Total preventive maintenance (TPM) as mediator. Therefore, it is important to obtain successful TQM paradigm. TPM acted as a prominent paradigm to improve the manufacturing performance to gain further competitive advantage. TPM focused on trying to on-going and minimize the error of production; Maintenance emphasize on maintain autonomously, equipment by production workers, in good condition. Hence, the purpose of this study is to mediator effect of TPM between TQM and business performance. Based on Federation of Malaysian Manufacturers (FMM) and the foreign companies’ directory list in Malaysia, 1500 companies have been selected for final survey. Of the 1500 surveys, 327 surveys, which were equivalent to 21.8% response rate, were returned. The result shows that TPM has been proved as partial mediator between TQM and business performance with indirect effect 0.25. The result will help manufacturing companies in improving TQM practices through TPM as mediator to compete in global market.